Perancangan Mesin Vakum dan Pengemasan Untuk Produksi Olahan Jamur Tiram Dalam Rangka Meningkatkan Nilai Jual dan Masa Pakai - Sir Anderson; Harfardi Harfardi; Feidihal Feidihal; Fiska Rahmi (Jurnal Teknik Mesin, 2021)
The design of this Vacuum and Packaging Machine is made in order to increase the sale value and service life for processed Oyster Mushroom products. Not only that, this machine can do packaging in a short time and efficiently. This machine consists of Frame, Vacuum Motor, Impulse Sealer, Vacuum Clamp. This Vacuum and Packaging Machine has dimensions of length 700 mm x width 500 mm x height 700 mm. The impulse sealer used is Arashi Ais 400 type by using a VE115N 2 CFM type vacuum motor. From this vacuum motor will later be connected to the vacuum clamp as a tool to clamp the packaging during the process of vacuuming the air in the package. This machine is equipped with a limit switch on the vacuum clamp that works to connect the current to the vacuum motor so that the vacuum motor automatically turns on. The operation of this vacuum and packaging machine is quite simple by inserting the packaging containing the product into the sealer and at the end of the package clamped on the vacuum clamp, the vacuum motor will automatically turn on, the next step is to operate the impulse sealer so that the product is finished packed under vacuum. From the design results, the bending stress of the frame is 3.172 N / mm2, the working time of the vacuum and sealer is 1.54 s per package, and the estimated price of the machine is Rp. 1,879,000